The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1086/427388
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Ancient Components in the Sculptor Dwarf Spheroidal Galaxy: First Results from the Dwarf Abundances and Radial Velocities Team

Abstract: We have found evidence for the presence of two distinct ancient stellar components (both ≥ 10 Gyr old) in the Sculptor dwarf spheroidal galaxy. We used the ESO Wide Field Imager (WFI) in conjunction with the VLT/FLAMES spectrograph to study the properties of the resolved stellar population of Sculptor out to and beyond the tidal radius. We find that two components are discernible in the spatial distribution of Horizontal Branch stars in our imaging, and in the [Fe/H] and v hel distributions for our large sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
414
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 347 publications
(473 citation statements)
references
References 22 publications
58
414
1
Order By: Relevance
“…Rather, there is a secondary, much more extended, lower surface brightness and lower luminosity component to the galaxy that surrounds the highly elliptical main body i.e., a stellar halo. Indeed, such a scenario is not particularly unusual; bright galaxies are known to possess multiple stellar components and more recent work on nearby dwarf galaxies suggests that multiple components are ubiquitous even at low stellar mass (e.g., Martínez-Delgado et al 1999;Lee & Kim 2000;Kleyna et al 2003;Tolstoy et al 2004;Kleyna et al 2004;Vansevičius et al 2004;Battaglia et al 2006Battaglia et al , 2008Battaglia et al , 2011McConnachie et al 2007a;Hidalgo et al 2008;Bellazzini et al 2014). We note that the recent analysis of Sag DIG by Beccari et al (2014) trace the profile to approximately 4 arcmin.…”
Section: On the Content And Structure Of Sag Digmentioning
confidence: 62%
“…Rather, there is a secondary, much more extended, lower surface brightness and lower luminosity component to the galaxy that surrounds the highly elliptical main body i.e., a stellar halo. Indeed, such a scenario is not particularly unusual; bright galaxies are known to possess multiple stellar components and more recent work on nearby dwarf galaxies suggests that multiple components are ubiquitous even at low stellar mass (e.g., Martínez-Delgado et al 1999;Lee & Kim 2000;Kleyna et al 2003;Tolstoy et al 2004;Kleyna et al 2004;Vansevičius et al 2004;Battaglia et al 2006Battaglia et al , 2008Battaglia et al , 2011McConnachie et al 2007a;Hidalgo et al 2008;Bellazzini et al 2014). We note that the recent analysis of Sag DIG by Beccari et al (2014) trace the profile to approximately 4 arcmin.…”
Section: On the Content And Structure Of Sag Digmentioning
confidence: 62%
“…However, recent observations have shown that the internal kinematics of these apparently simple stellar systems are more complicated than was first thought (e.g. Wilkinson et al 2004;Tolstoy et al 2004) with distinct stellar populations exhibiting different kinematic signatures.…”
Section: Observations Of Kinematic Substructure In Local Group Dsphsmentioning
confidence: 97%
“…Lee et al 2003;Harbeck et al 2001). Recently, Tolstoy et al (2004) have found that in the Sculptor dSph, differences in the spatial distribution of the stellar populations are mirrored by variations in the velocity dispersions of the populations. A preliminary analysis of our VLT-FLAMES data for the Carina dSph (see Koch -this proceedings -for a discussion of these data) provides hints of velocity substructure in this galaxy also.…”
Section: Observations Of Kinematic Substructure In Local Group Dsphsmentioning
confidence: 99%
“…These include Galactic globular clusters (e.g., Armandroff & Da Costa 1991;Da Costa & Armandroff 1995;Rutledge et al 1997;Saviane et al 2012), Galactic open clusters (e.g., Cole et al 2004;Warren & Cole 2009;Carretta et al 2009;Carrera et al 2015) and stars in the Galactic Bulge (e.g., Vásquez et al 2015). It has also been used to study both field stars and star clusters in the LMC (e.g., Olszewski et al 1991;Cole et al 2005;Carrera et al 2008a) and SMC (e.g., Da Costa & Hatzidimitriou 1998;Carrera et al 2008b;Parisi et al 2010;Dobbie et al 2014;Parisi et al 2015), as well as red giants in dwarf spheroidal (e.g., Armandroff & Da Costa 1991;Pont et al 2004;Tolstoy et al 2004;Battaglia et al 2008Battaglia et al , 2011 and dwarf irregular galaxies (e.g., Leaman et al 2013). …”
Section: Introductionmentioning
confidence: 99%